2019
DOI: 10.1371/journal.pone.0209851
|View full text |Cite
|
Sign up to set email alerts
|

A test of positive suggestions about side effects as a way of enhancing the analgesic response to NSAIDs

Abstract: Side effects are frequent in pharmacological pain management, potentially preceding analgesia and limiting drug tolerability. Discussing side effects is part of informed consent, yet can favor nocebo effects. This study aimed to test whether a positive suggestion regarding side effects, which could act as reminders of the medication having been absorbed, might favor analgesia in a clinical interaction model. Sixty-six healthy males participated in a study “to validate pupillometry as an objective measure of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 56 publications
1
18
0
2
Order By: Relevance
“…Two studies employed positive message framing, involving information that side effects were indicative of the drug working ( Wilhelm et al, 2018 ; Fernandez et al, 2019 ).…”
Section: Evidence To Datementioning
confidence: 99%
See 1 more Smart Citation
“…Two studies employed positive message framing, involving information that side effects were indicative of the drug working ( Wilhelm et al, 2018 ; Fernandez et al, 2019 ).…”
Section: Evidence To Datementioning
confidence: 99%
“… Fernandez et al (2019) administered the analgesic diclofenac with a side-effect-inducing agent (atropine) in healthy volunteers. Video instructions stated that experiencing side effects were an indication that the medication was active in the body and would help reduce pain (positive frame) or simply to inform staff if side effects were experienced (control frame).…”
Section: Evidence To Datementioning
confidence: 99%
“…The recent literature showed that theoretical and empirical evidence for the use of framing strategies could reduce the development of nocebo side effects with the rationale that positively framing such information could diminish this risk [25, 26]. Other authors suggest that the studies using multiple modes (including video, which comprises visual and verbal presentation methods) elicited numerically larger framing effect sizes, suggesting that multimodal presentation may more successfully elicit the framing effect [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with control groups given a standard, empathetic message about side effects, patients who were informed that side effects are a sign treatment is working were less anxious about side effects 8 and rated side effects as less threatening 6 and less intense. 7 Reducing threat, worry and intensity of side effects are powerful ways to improve overall treatment experience.…”
Section: State Of the Sciencementioning
confidence: 99%
“…Overall, 65% of participants preferred the latter. 7 This suggests that, when given an informed choice, most people prefer to have side effects explained as an indication of treatment efficacy.…”
Section: State Of the Sciencementioning
confidence: 99%